ANALISIS PELAYANAN RUMAH SAKIT UMUM DENGAN PERBANDINGAN ANTARA METODE ALGORITMA KMEANS, DAN K-MEDOIDS CLUSTERING - Christnatalis -; Eric Claudyo; Lucky -; Herry Kristover Manullang; Arus Iman Zebua (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
Hospitals are part of a health system that aims to provide comprehensive individual health services. Services include inpatient, outpatient, and emergency care. Hospitals must provide high-quality services according to existing standards and serve all levels of society. Understanding customers' needs, wants, and demands will provide Another factor that affects the quality of health services is the availability of resources and service facilities during the insurance period. Lack of continuity of service affects the efficiency and quality of the relationship. The quality of health services is also strongly influenced by the ease of information and timeliness of public hospital services. Based on data from 341 hospital service quality surveys, the results obtained from the K-Means algorithm method are 2.701288, while the results obtained in the K-Methoids Clustering method are 2.17, where the General Hospital service questionnaire is a very satisfied category. A comparison of the results of the K-Means and K-Medoids methods aims to make it easier to measure customer satisfaction.